Проблеми мотивації формування інтелектуального капіталу підприємств будівельного комплексу - Гольда, А. В. (Ways to Improve Construction Efficiency, 2012)
The article determines the most actual problems of the motivation of domestic intellectual capital formation of building complex in term of transition to the innovation development model. The attention is devoted to system motivation of intellectual capital of building complex and legislative – regulatory framework improvements.